Importance of the JAK/STAT signaling pathway in sepsis - Torres-Carpio, Daniel Alfonso (2022)
The Janus-Kinase signal transducer and the transcription activation pathway known as JAK /STAT is a major signaling pathway for the transduction of information in many inflammatory cytokines involved during sepsis. The JAK / STAT pathway has been shown to be strongly related to multiorgan failure, and many cytokines can exert their biological effects through this pathway. In recent years, considerable progress has been made in understanding functions of this complex; however, its role in sepsis as a therapeutic target remains under experimentation. This review describes the specific functions of the JAK / STAT pathway, its role in sepsis, and presents a translational approach to the therapeutic perspective aiming to inhibit this signaling pathway during sepsis and its interaction with inflammatory diseases such as COVID-19.